Sea-ice permittivity derived from GNSS reflection profiles: Results of the MOSAiC expedition - Semmling, Maximilian; Wickert, Jens; Kreß, Frederik; Hoque, Mohammed Mainul; Divine, Dmitry; Gerland, Sebastian; Spreen, Gunnar (IEEE Transactions on Geoscience and Remote Sensing, 2021)
Reflectometry measurements have been conducted aboard the German research icebreaker Polarstern during the MOSAiC expedition (Multidisciplinary drifting Observatory for the Study of Arctic Climate). Signals of Global Navigation Satellite Systems (GNSS) were recorded using a dedicated GNSS reflectometry receiver for retrieval of sea-ice reflectivity. The primary goal is a reflectometry-based monitoring of sea ice as part of the Arctic climate study. The data set presented here covers the expedition's first leg (late Sep. to mid Dec. 2019) in the Siberian Sector of the central Arctic (at about 82°N to 87°N). Daily profiles of reflectivity are retrieved for satellite elevations < 45°. In agreement with model prediction the results show best reflectivity contrast (about 5 dB between compact pack-ice and lower ice concentrations) for observations at left-handed circular polarization and elevation angles of 10° to 20°. A daily resolved time series of sea-ice relative permittivity is inverted from the left-handed data. In general, the level of inversion results is at the lower limit of sea-ice values (rel. permittivity of 3 and below), potentially indicating an influence of incoherent volume scattering. Occasional increase of relative permittivity is attributed to the presence of water. Sea-ice profiles show anomalies that are confirmed by enhanced model prediction (slab reflection). A long-term comparison of prediction and retrieved profiles indicates anomalies' dependence on ice thickness and temperature.